(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The research aims to shed light on the amount of proceeds annual tax for each of the way the contract total and percentage of completion method - see which is better - as well as the current problems arising from the application method of the contract in full in settling accounts tax - to identify problems - related to postpone settling accounts tax in accordance with the way the contract fully and determine the advantages and disadvantages of each of the methods through practical application , and then use the results as inputs to help in the decision to confirm the continuation of the GCT using a full decade in settling accounts tax for long-term construction contracts or forgo them. Were the result of research the existence of a fiscal gap in proceeds annual tax due to divergence value of income subject to the charge of tax for each of the two methods , have concluded search to a set of conclusions , including that the adoption of the way the contract in full , accompanied by many problems as it is not the best way for approval in settling accounts tax for this type of activity and contracts , as well as a set of recommendations , including the possibility of adopting the percentage of completion method of tax charge for this type of activity and contracts.